ABCE1 facilitates tumour progression via aerobic glycolysis and inhibits cell death in human colorectal cancer cells through the p53 signalling pathway - Sathan Raj Natarajan; Rajapandiyan Krishnamoorthy; Mohammad A Alshuniaber; Tawfiq S Alsulami; Mansour K. Gatasheh; Ponnulakshmi Rajagopal; Chella Perumal Palanisamy; Ramajayam Govindan; Vishnu Priya Veeraraghavan; Selvaraj Jayaraman (Scientific Reports)
Abstract Colorectal cancer (CRC) poses a formidable challenge to global health, necessitating the quest for novel biomarkers to improve therapeutic strategies. This study explores ABCE1 (ATP-binding cassette subfamily E member 1) as a potential biomarker for CRC and delves into its intricate molecular mechanisms. Through integrated bioinformatic analyses, this study underscores the significant oncogenic role of ABCE1 in CRC, opening new avenues for promising therapeutic interventions. Deletion of ABCE1 reduced cell growth, abrogated aerobic glycolysis, and promoted apoptosis in HT-29 and HCT-116 cells. Further validation through experimentation with irinotecan revealed compelling outcomes, including diminished cell growth, induces G1 phase cell cycle arrest, and promotes apoptosis in HCT-116 and HT-29 colorectal cancer cells. ABCE1 KO with irinotecan combined treatment significantly increased the inhibition of cell proliferation and aerobic glycolysis in CRC cells, accentuating the multifaceted role of ABCE1 in CRC progression. Moreover, this work also demonstrated the complex relationship between ABCE1 and the p53 signalling pathway, which was confirmed in experimental assays. These assays also revealed that deletion of ABCE1 with irinotecan might regulate G1 phase cell cycle arrest, inhibit metabolic regulation, and activate the p53 pathway to induce apoptosis in HCT-116 cells. Molecular docking analyses further supported these findings, revealing the strong binding affinity of irinotecan for targets of the p53 signalling cascade. Collectively, these comprehensive insights support the potential therapeutic efficacy of targeting ABCE1 in CRC treatment strategies. Overall, the findings from this study underscore the importance of ABCE1 as a potential biomarker in CRC and illuminate its complex molecular mechanisms. The demonstrated effectiveness of ABCE1 inhibition, particularly through irinotecan, coupled with its interplay with crucial signalling pathways such as p53, highlights its potential as a promising therapeutic option for colorectal cancer treatment.